Spectrum and risk factors for upper gastrointestinal bleed: an experience from multilevel teaching hospital of North India - Khan, Farhan; Gupta, Ajesh Chandra; Giri, Richa; Kumar, Vinay (International Journal of Advances in Medicine, 2023)
Background: The aetiology of upper gastrointestinal bleed is variable in different geographical regions. Epidemiological data are helpful in knowing the burden of the problem. This study was conducted to know the etiological spectrum, mortality, morbidity, and predictors of outcome in patients with acute UGIB. Methods: Cross-sectional observational study to be carried out in indoor patients presenting with upper GI bleed and to study the spectrum and risk factors associated with it at LLR and associated hospitals, GSVM Medical College, Kanpur during 2020-2022 and noted the clinical presentation, aetiology of bleed, and outcome. Results: Out of 120 patients, 60(50%) had history of chronic alcohol intake, use of NSAIDS 12(10%), smoking 7 (5.83%), intake of spicy food 7 (5.83%), use of steroids 3 (2.5%), stressor present 3 (2.5%), not identified 10 (8.33%). Maximum no. of cases presenting with upper Gi bleed had oesophageal varices 55 (45.83%), esophagitis/gastritis/duodenitis 36 (30%), carcinoma upper GI 12 (10%) normal 11 (9.16%) GAVE 2 (1.66%) Mallory Weiss tear 4 (3.33%). Conclusions: In our study it was found that the most common risk factor for upper GI bleed is chronic alcohol intake and the most common endoscopic finding in these patients were variceal bleed.